Isu-isu Pendidikan di Luar Sekolahan (Keluarga dan Masyarakat) - Supatmi, Supatmi; Sukari, Sukari (TSAQOFAH, 2024)
This paper aims to explore the issues of education outside of school commonly encountered in families and communities. The research utilizes a Systematic Literature Review (SLR) approach to collect various literature and journals. The findings of this study indicate that efforts in education beyond the school setting can be pursued through families, communities, and various other initiatives. This is done to safeguard the mental health of children from an early age and for their future well-being.